Femme fatale in the Dramas of the Imperial-Royal Monarchy: from Wedekind and Wyspiański to Robida and Cerkvenik - Kozak, Krištof Jacek (Slavia Centralis, 2024)
The motif of women who with their seductiveness fatally influence men has a long history in the art world but they (as femmes fatales) became particularly distinct as they entered fin de siècle art in Vienna. The characters of F. Wedekind, A. Schnitzler or O. Kokoschka thus became paradigmatic, and their influence spread to the borders of the monarchy, where they were adapted in various ways. While a review of Polish literary works (S. Przybyszewski, S. Witkiewicz, S. Wyspiański) shows that these authors adopted a much less fatal and destructive version of the femme fatale, Slovenia (E. Gangl, A. Robida, A. Cerkvenik), in contrast, developed her most radical – fatal, or even satanic – version.